ASUHAN KEBIDANAN IBU BERSALIN DAN BBL NORMAL DI RUANG VK KLINIK UTAMA NILAM SARI TEMBILAHAN TAHUN 2019 - Jamilah; Madinah (Jurnal Kesehatan Husada Gemilang, 2022)
The number of maternal deaths In Indragiri Hilir Regency in 2018 was 9 people and neonates 21 people. The high death rate of mothers and neonates is expected to be able to carry out their duties professionally and qualifiedly. The purpose of this care is able to provide comprehensive midwifery care services to maternity mothers and newborns at Mrs"S" G3P2A0H2 gestational age 39 weeks in accordance with obstetrics management in the VK room of Nilam Sari Tembilahan Main Clinic on July 29, 2019. This upbringing uses varney's documented 7-step management in SOAP form. The result of obstetric care there is a gap between theory and practice that is not in accordance with the 60-step guidelines of APN, namely not assessing DJJ every uterine contraction completed because the head decline is rapid, does not do an overall assessment because there is still care to be done, the early initiation of breastfeeding is not up to 1 hour because the mother has refused and lack of knowledge about the benefits of the early initiation of breastfeeding, Not immunizing hepatitis B 1 hour after vitamin K because it provides the injection distance to the baby and the maximum dilation phase to the deceleration phase is only 1 hour because it is strong. Health workers are expected to improve services in providing midwifery care in accordance with the 60-step APN guidelines in order to reduce existing gaps and explain the benefits of care provided.